Crab Ash Extract has Anti-Proliferative Effects on SK-MEL-28 Melanoma Cells and Induces a Cellular Stress Response and Metabolic Changes - Katran, Hedeel; Brestovac, Brian; Dye, Danielle (2019)
The incidence of metastatic melanoma continues to rise worldwide and although there has been recent advances in treatment, outcomes remain poor for many patients. Therefore, there remains a need for novel treatments. Recently, in vitro studies have shown that some compounds derived from crab shell or hemolymph may have anticancer properties. Furthermore, whole crab ash has been recorded as a traditional folk medication used to treat solid tumours. This study examined the anticancer properties of extracts derived from the crab genus Portunus. The SK-MEL-28 melanoma cell line was treated with ethanol and aqueous extracts derived from whole crab ash (CA), shell, or muscle fibres. Concentrations tested were from 312.5 µg/mL to 5000 µg/mL. CA ethanol extract showed the highest amount of cell death, with 100% cell death observed at 2500 µg/mL and 50% cell death at 1250 µg/mL. Cells that survived CA treatment showed altered morphology and intracellular granulation. Next, lysates of melanoma cells treated with a sub-lethal concentration (750 µg/mL) of ethanolic CA were analysed by semi-quantitative mass spectrometry. This revealed upregulation of proteins associated with protein synthesis, folding and degradation, ER chaperones, carbohydrate and lipid metabolism, cytoskeletal and some nuclear proteins. Taken together, the proteomic data suggest activation of cellular stress pathways and changes in metabolism.